(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, UGMH GdLhGgQ, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s ((3ESeGYjd GdfLa BHGOjs)
(3ChdgG (B:s
...(3ef GdCbSGe GdCQHYI GdJj Hfj YdjgG GdcJGH aj GdYbhO(B...s
(3BNQgG (B:s
...(3hCeG GdKGfj agh hGVM GdaSGO hMed GdYHGQI Ydi Pdc eecf hEf cGf HYjOG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B92s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B378s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis